Modal Sosial dan Human Capital Sebagai Alat Untuk Meningkatkan Kinerja Pemasaran - Eviatiwi Kusumaningtyas Sugiyanto; Mira Meilia Marka (University of Merdeka Malang, 2017)
The aim of this research are to analyze how human capital and marketing performance can be improved through social capital, both internally and externally Quota sampling method are used to seeing the responses of 140 Batik SME’s in Semarang related research quetions. This research used Structural Equation Model (SEM) under Amos 22.0 program as analysis tools. This research indicated that 1) internal social capital positively effect on human capital, 2) external social capital positively effect on human capital, 3) external social capital has no effect on marketing performance, 4) internal social capital positively effect on marketing performance, and 5) human capital positively effect on marketing performance https://doi.org/10.26905/jmdk.v5i2.1642